Faktor-Faktor Ideal Perusahaan Dalam Pelaksanaan CSR (Corporate Social Responsibity) - Herman, Herman; Novarizal, Riky (Sisi Lain Realita, 2017)
Corporate social responsibility (CSR) is an act that the company does to the public in general in the context of empowerment. The main actors involved in the implementation of this CSR is all stakeholders who work in sync for the sustainable development. The implementation of CSR has many aspects, such as sustainable development in the framework of community empowerment. For the smooth implementation of CSR is necessary some of the factors that support the implementation of CSR namely Building human capital, Strengthening economics, Assessing social cohesion, Encouraging governance, Protecting the environment, Two ways.